Prevalence of Pneumonia Severity in Children under 5 Years Old at Primary Health Care of Tambakrejo, Surabaya - Shofia Ihtasya; Retno Asih Setyoningrum; Deby Kusumaningrum (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Pneumonia is the world-leading cause of death in children under five years old and most prevalent in developing country. Proper initial diagnosis will determine further management, because pneumonia and severe pneumonia have different treatment. The aim of this study was to describe the prevalence of pneumonia severity in children under five years old at primary health setting. Methods: This study was a cross – sectional descriptive study on medical records of children aged 2 to 59 months with pneumonia at primary health care of Tambakrejo, Surabaya from September to December 2017. Severity of pneumonia is classified using its clinical sign such as fast breathing, fever, chest indrawing, and general danger sign. The data were processed using Microsoft Office Excel and statistically analyzed with SPSS IBM 20. Results: There were 31 respondents that were diagnosed with pneumonia at primary health care of Tambakrejo, Surabaya from September to December 2017. Most of the children diagnosed with pneumonia were aged 12 to 59 months (61.3%) and 22.6 % of the children had severe pneumonia. Conclusion: Distribution of severity case of pneumonia at primary health care of Tambakrejo, Surabaya showed that there were more case of pneumonia with fast breathing than severe pneumonia or pneumonia with any general danger sign. Most of them were diagnosed at 12 to 59 months with a good nutritional status.